2018 ESC/EACTS guidelines on myocardial revascularization - Franz-Josef Neumann; Miguel Sousa-Uva; Anders Ahlsson; Fernando Alfonso; Adrian P. Banning; Umberto Benedetto; Robert A. Byrne; Jean-Philippe Collet; Volkmar Falk; Stuart J. Head; Peter Jüni; Adnan Kastrati; et al. (Российский кардиологический журнал)
Developed with the special contribution of the European Association of Percutaneous Cardiovascular Interventions (EAPCI)